Sintering of tin oxide using zinc oxide as a densification aid - Foschini, C. R.; Perazolli, L.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2004)
The physicochemical electronic characteristics of SnO2 render it useful in many technical applications, including ceramic varistors, stable electrodes used in electric glass-melting furnaces and electrometallurgy of aluminum, transparent windows and chemical sensors. The use of ZnO as a sintering aid was explored in this study to obtain SnO2 as a dense ceramic. Compacts were obtained by mechanical mixing of oxides, isostatic pressing at 210 MPa and sintering in situ inside a dilatometer at heating rates of 10degreesC/min. The grain size and microstructure were investigated by scanning and transmission electron microscopy (SEM/TEM). The phases and chemical composition were analyzed by energy dispersive spectroscopy (EDS) and X-ray diffraction (XRD). The results indicated that ZnO acts as a densification aid for SnO2, improving its grain growth with additions of up to 2 mol%. ZnO forms a solid solution with SnO2 UP to 1 mol%, above which SnZnO3 precipitates in the grain boundary, potentially inhibiting shrinkage and grain growth. (C) 2004 Kluwer Academic Publishers